Weighing the Risks of Nuclear Energy and Climate Change: Trust in Different Information Sources, Perceived Risks, and Willingness to Pay for Alternatives to Nuclear Power. Issue 3 (28th June 2016) - Vainio, Annukka; Paloniemi, Riikka; Varho, Vilja
Abstract : We examined how individuals perceive nuclear energy in the context of climate change mitigation and how their perceptions are associated with trust in different risk information sources. We analyzed the interrelationships between trust, perceived risk of nuclear power, climate change concern, perception of nuclear energy as an acceptable way to mitigate climate change, and willingness to pay (WTP) for alternatives to nuclear power. A nationwide survey ( N = 967) collected in Finland was analyzed with structural equation modeling. The associations between trust and perceived risk of nuclear power, climate change concern, and perception of nuclear power as a way to mitigate climate change varied by the type of information source. Political party support and other background variables were associated with trust in different information sources. The effect of trust in information sources on WTP was mediated by perceived risks and benefits. The results will increase our understanding of how individuals perceive nuclear energy as a way to cut CO2 emissions and the role of trust in different information sources in shaping nuclear risk perceptions and energy choices.